Propuesta pedagógica de juegos recreativos para desarrollar la motricidad gruesa en estudiantes de 4to año de la Unidad Educativa Particular “Santa Mariana de Jesús” 2023-2024. - Sánchez Maurat, René Daniel (2024)
The present work of curricular integration was carried out with the objective of: Develop a pedagogical proposal for recreational games to improve gross motor skills in students of 4th year parallel "B" of Basic General Education of the Private Educational Unit "Santa Mariana de Jesús", in the period 2023-2024. A mixed approach was used, with a quasiexperimental design and correlational scope, employing deductive and inductive methods, as well as direct observation. Diagnostic instruments, such as tests, were administered to a sample of 22 students. The results obtained from the diagnostic instruments highlight the importance of recreational games in education, because they stimulate both the mental and physical state of students, promoting the development of motor, social, cognitive and creative skills. Therefore, it is essential to include them in the plans and provide opportunities for students to enjoy and learn through them. Based on these effects, a pedagogical proposal based on recreational games was designed and implemented, consisting of 8 class sessions with activities related to gross motor skills. Control instruments were applied, showing improvement in the aforementioned aspects. It was concluded that the students initially had a low level of coarse motricity, but with the implementation of the proposal and the use of Arnhem Sinclair's post-test for the development of coarse motricity, most students improved their motricity, increasing at least one point in each of the 6 tests. Therefore, the results obtained support the effectiveness of the pedagogical proposal, demonstrating the effectiveness of recreational games as a strategy for the development of gross motor skills. Keywords: recreational games, gross motor skills, pedagogical proposal.